Diesel : - Toboldt, William King (Goodheart-Willcox Co., 1980)
The book covers the construction, operation, service, and repair of two- and four-stroke diesel engines. This textbook details developments in engine control computers, fuel management systems, and emission control systems. Content relates to on- and off-road vehicles, as well as marine, agricultural, and industrial applications.